2020
DOI: 10.3390/su12072804
|View full text |Cite
|
Sign up to set email alerts
|

Using Building Information Modelling to Manage Client Requirements in Social Housing Projects

Abstract: This paper proposes a set of guidelines for using Building Information Modelling (BIM) to manage client requirements in the context of social housing projects. A process model representing main activities involved in requirements management has been devised, as well as nine constructs that can be used for assessing the effectiveness of using BIM for client requirements management. The process of managing and modelling clients’ requirements is important to improve value generation, considering the limited resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
0
27
0
2
Order By: Relevance
“…In the empirical study, 56% of requirements were assessed in a semi-automated way while 44% could be translated into logical rules by using Solibri or dRofus, enabling fully automated assessment. The more automated the design assessment is, the longer the time designers will have to improve design solutions (Baldauf et al, 2020).…”
Section: Partial Assessment Of the Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the empirical study, 56% of requirements were assessed in a semi-automated way while 44% could be translated into logical rules by using Solibri or dRofus, enabling fully automated assessment. The more automated the design assessment is, the longer the time designers will have to improve design solutions (Baldauf et al, 2020).…”
Section: Partial Assessment Of the Methodsmentioning
confidence: 99%
“…Explicit requirements and specifications must then be stored (Kiviniemi, 2005;Shen et al, 2013;Jallow et al, 2014), refined, communicated, prioritized by decision makers and, finally, be used to assess design compliance (Shen et al, 2013;Jallow et al, 2014). Baldauf et al (2020) proposed a process model with interrelated activities involved in client requirements management with the support of BIM for the context of social housing projects. Those authors also identified benefits of using BIM in client requirements management, which are summarised in Table 2.…”
Section: Operation Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to researchers such as Whelton, Ballard [7], Winch, Usmani [8], one of the main reasons for this problem is the poor communication between designers and clients. This issue is even more challenging since achieving effective communication is highly more complex and challenging in hospital projects [9,10] because in such projects, there are multiple clients such as users (clinicians, patients, etc. ), managers, and/or the government (paying client).…”
Section: Introductionmentioning
confidence: 99%